2015
DOI: 10.1093/her/cyv023
|View full text |Cite
|
Sign up to set email alerts
|

A block randomized controlled trial of a brief smoking cessation counselling and advice through short message service on participants who joined the Quit to Win Contest in Hong Kong

Abstract: The present trial examined the effectiveness of brief interventions for smokers who joined the Hong Kong Quit to Win Contest to quit smoking. A block randomized controlled trial allocated 1003 adult daily smokers to three groups: (i) The TEL group (n = 338) received a 5-min nurse-led telephone counselling; (ii) The SMS group (n = 335) received eight text messages through mobile phone and (iii) The CONTROL group (n = 330) did not receive the above interventions. Participants with biochemically verified abstinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 29 publications
1
65
0
Order By: Relevance
“…Among the 22 in the intervention group who received Brief Advice, 6 (27%) respondents continued to quit smoking up to 6 months compared to none in the control. These findings are also consistent with similar study one quitting conducted by a Hong Kong researchers that showed that telephone-based advice was positively associated with abstinence in comparison to advice via short messaging service or no advice at all [18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among the 22 in the intervention group who received Brief Advice, 6 (27%) respondents continued to quit smoking up to 6 months compared to none in the control. These findings are also consistent with similar study one quitting conducted by a Hong Kong researchers that showed that telephone-based advice was positively associated with abstinence in comparison to advice via short messaging service or no advice at all [18].…”
Section: Discussionsupporting
confidence: 91%
“…More recently, randomized controlled trials on smoking cessation have been conducted in low-middle income countries settings. A Hong Kong study on the duration of abstinence that used cash incentive as a reward for quitting showed that a brief telephone advice was positively associated with abstinence while short service messaging and no intervention had no effect [18]. A new study protocol by Indian researchers on the effect of brief advice, including training in craving control, has been published [19].…”
Section: Introductionmentioning
confidence: 99%
“…Regular messages alone were not found to be effective in increasing abstinence in our previous QTW trial. 19 The counsellors who delivered the chat-based intervention were research staff with at least 1 year of experience in smoking cessation research, supervised by an MSclevel psychotherapist trained in ACT and by a research nurse (TTL). The counsellors met at least once weekly to discuss the caseloads.…”
Section: Methodsmentioning
confidence: 99%
“…We did a two-arm, parallel, pragmatic, clusterrandomised, controlled trial nested within a Quit to Win (QTW) smoke-free community campaign, organised by the Hong Kong Council of Smoking and Health. [16][17][18][19][20] Details of the rationale and study protocol were reported elsewhere. 21 Ethical approval was granted by the University of Hong Kong and the Hospital Authority Hong Kong West Cluster Institutional Review Board (UW .…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…7 8 However, brief advice had a small and non-significant effect on quitting outcomes, as most quit attempters still did not use cessation services or medications for quitting. [9][10][11] We propose to deliver cessation aids such as nicotine replacement therapy (NRT) sample to further enhance their motivation to quit and take real action. NRT is a safe pharmacotherapy that replaces the nicotine usually provided by smoking cigarettes, to reduce craving and withdrawal symptoms 12 and increase long-term abstinence.…”
Section: Open Accessmentioning
confidence: 99%